GREEN MARKETING: INNOVATIVE MANTRA OF MARKETING - Dr.M. VEERALAKSHMI (International Journal of Advanced Science and Technology, 2020)
The preservation and protection of our ecology pose a crucial challenge to business houses as wellas to the society. It is believed that environmentalism will emerge as one of the critical issues thatproducers and marketers will need to integrate into their activities for successful operations and betterresults in the long run. Thus, concern over the environment has emerged as an important topic in the fieldof marketing. In the practice of marketing, the phrase 'green marketing' has become quite popular. Theconceptualizing of green marketing re-evaluates the very tenants of our consumption society. Withoutcontinued support from the physical environment, the means to satisfy the needs and wants of consumerswill be curiously absent.